Monitoring of cure kinetic prepreg and cure cycle modeling - Costa, M. L.; Botelho, E. C.; Rezende, M. C. (Springer, 2006)
Cure kinetic model is an integral part of composite process simulation, which is used to predict the degree of curing and the amount of the generated heat. The parameters involved in kinetic models are usually determined empirically from isothermal or dynamic differential scanning calorimetry (DSC) data. In this work, DSC and rheological techniques were used to investigate some of the kinetic parameters of cure reactions of carbon/F161 epoxy prepreg and to evaluate the cure cycle used to manufacture polymeric composites for aeronautical applications. As a result, it was observed that the F161 prepreg presents cure kinetic with total order 1.2-1.9. (c) 2006 Springer Science + Business Media, Inc.